POTENTIAL, CHALLENGES, AND PROSPECTS FOR PAKISTAN’S BLUE ECONOMY - UR REHMAN, MUNIB (Journal of Maritime Logistics, 2023)
The value of water and oceans in fostering inhabitation and facilitating trade and economic connectivity is immense. Sea-trade has historically played a crucial role in building a state’s economic power. Pakistan, with over 1000 km of coastline and an extended Exclusive Economic Zone covering 290,000 sq.km, possesses abundant marine, fisheries, mineral, and energy resources that can generate significant revenues. Additionally, Pakistan’s geo-oceanic position offers vast opportunities for sea-based activities like transportation, tourism, shipbuilding, port facilities, and renewable energy. This paper highlights the challenges and prospects of Pakistan’s Blue Economy, providing policy recommendations for its development.